Business ethics and continental philosophy - Painter-Morland, Mollie; Bos, Rene ten. (Cambridge, UK : Cambridge University Press, 2011)
'Business ethics has largely been written from the perspective of analytical philosophy with very little attention paid to the work of continental philosophers. Yet although very few of these philosophers directly discuss business ethics, it is clear that their ideas have interesting applications in this field. This innovative textbook shows how the work of continental philosophers - Deleuze and Guattari, Foucault, Levinas, Bauman, Derrida, Levinas, Nietzsche, Zizek, Jonas, Sartre, Heidegger, Latour, Nancy and Sloterdijk - can provide fresh insights into a number of different issues in business ethics. Topics covered include agency, stakeholder theory, organizational culture, organizational justice, moral decision-making, leadership, whistle-blowing, corporate social responsibility, globalization and sustainability. The book includes a number of features designed to aid comprehension, including a detailed glossary of key terms, text boxes explaining key concepts, and a wide range of examples from the world of business'--
'MOLLIE PAINTER-MORLAND AND RENE TEN BOS Why read this book? Authors like to imagine that people read their books out of passion for the subject matter or at least out of a curiosity regarding the new perspectives that the text may yield. Years of teaching have, however, made this team of editors more realistic. This book was more likely assigned by your teacher, and bought with hard-earned money squeezed from an increasingly tight textbook budget. You are most likely opening it now because your teacher assigned the introduction for your first class meeting, or because you are eager, or anxious, or both, to know what will be expected of you in this course within the next few weeks. The other possibility is that you are a teacher yourself, trying to determine what your students should spend their money and time on. It is therefore pointless to convince you that this book is worth the money you or your students have spent and the time that all of you will devote to reading it over the next couple of weeks. We cannot convince you, even if we tried. Reading books is a uniquely personal activity. The journey that reading this book will take you on is shaped by who you are and by what you bring to the table in terms of questions, passions, and expectations. The best we can do is try to explain why we went to the trouble of putting this book together.'--
Includes bibliographical references and indexes.
Keywords: Business ethics; Corporate culture; Social responsibility of business